Risk Management Implementation in Mitigating Non-Performing Financing at Bank Syariah Indonesia - Muhamad Dipo Misnadi; Maya Sari (Riviera Publishing, 2026)
This study analyzes the implementation of risk management frameworks in mitigating Non-Performing Financing (NPF) at Bank Syariah Indonesia (BSI), addressing a critical challenge to the sustainable growth of Islamic banking. Employing a descriptive qualitative approach through in-depth interviews with key stakeholders and comprehensive document analysis, this research identified that BSI’s risk management strategy is built upon three primary pillars: (1) robust creditworthiness assessments utilizing the 5Cs of credit analysis alongside deep character evaluation, supported by stringent Risk Acceptance Criteria (RAC) and rigorous verification; (2) proactive monitoring systems and tight internal controls deployed via a digitalized Early Warning System (EWS) and strategic payment due-date adjustments; and (3) an integrated, Sharia-compliant NPF resolution mechanism utilizing rescheduling, reconditioning, and restructuring protocols. The findings reveal a consistent downward trend in BSI’s NPF ratio, demonstrating the efficacy of a risk management policy that is adaptive, digitally-driven, and anchored in Sharia principles, including the vital oversight of the Sharia Supervisory Board. This study enriches the literature on Islamic banking risk management by highlighting the integration of Sharia dimensions into credit risk mitigation, while offering practical insights for BSI and other Islamic financial institutions to optimize financing portfolio quality and strengthen overall financial stability.